Szkolnictwo wyższe i dyplomacja naukowa jako narzędzie soft power w polityce ChRL wobec Unii Europejskiej - Kościelniak, Cezary (Przegląd Politologiczny, 2018)
Higher education policy is an element of soft power in the international politics of the PRC. This has become possible because, for two decades, universities in China have been developing and undergoing profound changes. PRC authorities have set ambitious goals for their universities, e.g. making some of the universities top higher education institutions worldwide. Universities in China are abandoning the “copy-paste” pattern, developing their own technological innovations, and consistently raising their position in international rankings. Development goals set for Chinese universities are connected with the global economic expansion of the PRC. The scientific diplomacy of China is primarily executed through the Confucius Institutes network. European Union universities are a strategic goal of this policy as they possess the resources, practices and customs China needs to strengthen its universities. The paper analyzes selected issues of employing higher education policy as a soft power in Chinese diplomacy.